Contra o tempo : filosofia prática do instante - Concheiro, Luciano (CLACSO, Consejo Latinoamericano de Ciencias Sociales, 2018)
"To tell our days Luciano Concheiro appeals to a limited but incisive writing, adjusted to these interrupted reading times. His reflections reach readers in small, brief and concise capsules, endowed with a syntax that is as clear as it is revealing. In the realm of the short term, its truths can be read in an instant." From the prologue by Pablo Gentili and Nicolás Arata